Challenges and Triumphs: The International Expansion of Japanese Regional Food Businesses - Ming, Lau Chung (Advances in Social Sciences Research Journal, 2026)
The global proliferation of Japanese restaurants has extended beyond large corporations to include numerous regional businesses that have successfully ventured into international markets. This research investigates the challenges and opportunities encountered by a regional ramen shop in establishing its inaugural international location in South East Asia country. Through interviews with marketing representatives and a site visit, the study provides insights into the operational dynamics and market adaptation strategies employed by the shop. Despite its success in Japan, the establishment faced significant difficulties in another market, primarily due to inadequate market research, a limited menu variety, and pricing strategies that did not align with local consumer expectations. Initial efforts to attract customers involved revising the menu to incorporate local flavors; however, these adjustments were insufficient, ultimately leading to the closure of the first overseas location. The findings underscore the critical importance of conducting comprehensive market research, tailoring menu offerings to local tastes, and selecting optimal locations for international expansion. Recommendations for future ventures include developing responsive pricing strategies, engaging with local communities, and training staff on cultural sensitivity. By adhering to these guidelines, regional Japanese food restaurants can improve their prospects for successful international expansion and cultivate a loyal customer base in diverse markets.